Issues of Teacher Performance Stability are Not New: Limitations and Possibilities - Thomas L. Good; Alyson L. Lavigne (Education Policy Analysis Archives, 2015)
Morgan, Hodge, Trepinski, and Anderson (2014) have written an article that continues to confirm what we have known for some time—teacher effects on student achievement have limited stability. In this commentary, we address the other potential contributions this work can make to inform practice, policy, and research. While illustrating Morgan et al.’s inattention to history, we take the opportunity to reframe their findings. Considering the authors’ work in the context of past and current research, we illustrate that this collective set of stable evidence should convince policymakers that it is not reasonable to assume that teachers and teaching is stable across time. Beyond this important opportunity to influence policy, we believe these findings underscore the need to build upon and expand the dependent measures we use to define and understand good teaching. After all, as we have noted (Lavigne Good, 2014; in press) good teaching involves much more than increasing students’ scores on standardized achievement tests.